Metastasis of Breast Cancer Promoted by Circadian Rhythm Disruption due to Light/Dark Shift and its Prevention by Dietary Quercetin in Mice. Issue 1 (18th February 2021) - Numata, Minoru; Hirano, Akane; Yamamoto, Yukika; Yasuda, Michiko; Miura, Nobuhiko; Sayama, Kazutoshi; Shibata, Masa-Aki; Asai, Tomohiro; Oku, Naoto; Miyoshi, Noriyuki; Shimoi, Kayoko
Epidemiological studies have indicated that a disturbed circadian rhythm resulting from night-shift work is a potential risk factor for breast cancer. However, the mechanism of increased risk of breast cancer by night-shift work remains unclear, and there have been few in vivo studies conducted to definitively associate the two factors. In this study, BJMC3879Luc2 mouse breast cancer cells were transplanted into BALB/c mice. Mice were maintained under lighting conditions that modeled the two-shift system and were investigated for the effect of light/dark cycle disruption on tumor growth and lymph node metastasis. Circadian dysfunction, which was confirmed by measuring circadian locomotor activities using a nano tag device in our light/dark shift model, did not affect tumor growth. However, a significant increase in the number of lymph nodes with distant metastasis was observed. Neutrophil-to-lymphocyte ratio, which is an adverse prognostic factor of breast cancer and also indicator of inflammation, also increased. It has been demonstrated that a chronic inflammatory response is associated with cancer malignancy and poor prognosis in various cancers. These results suggest that night-shift work may also affect distant metastasis and prognosis. In addition, we investigated whether dietary quercetin has anti-metastatic activity against light/dark shift-induced metastasis. A diet containing 0.3 % quercetin significantly inhibited distant lymph node metastasis, particularly metastasis to the iliac and kidney lymph nodes. Our results contribute to our understandings of the effects of the external light environment on breast cancer metastasis and provide a glimpse into potential protective effects of dietary quercetin on light/dark disturbance-induced metastasis.